Феномен пограниччя в умовах "війн ідентичностей": трансформаційна динаміка та евристичний потенціал - Верменич, Я.В. (Вісник НАН України, 2023)
У статті розглянуто евристичний потенціал феномену пограниччя в контексті осмислення конфліктогенних чинників соціокультурного розвитку
прикордонних територій і трансформаційної динаміки ідентифікаційних
стратегій порубіжних соціумів. Репрезентовано діапазон можливостей
застосування концепцій пограниччя у дослідженні як сучасних українських
реалій, так і трансформацій просторового розвитку України в історичній
ретроспективі. Актуалізація проблеми зумовлена пошуком шляхів подолання викликів, пов’язаних із російсько-українською війною, розробленням
алгоритмів виявлення руйнівних процесів, що здатні деформувати соціокультурну динаміку українського суспільства. Застосування синергетичних підходів нової «кордонної філософії» відкриває шлях до усвідомлення
просторової інваріантності та полікультурності як факторів впливу на
суспільні цінності й поведінкові реалії. The article considers the heuristic potential of the border phenomenon in the context of understanding the conflictgenerating
factors of socio-cultural development in border areas and the transformational dynamics of identification
strategies of border societies. The range of possibilities for application of border concepts in the study of both modern
Ukrainian realities and transformations in spatial development of Ukraine in historical retrospect is represented. The
relevance of the problem is due to the search for ways to overcome the challenges associated with the Russian-Ukrainian
war, the development of algorithms for identifying destructive processes that can distort the socio-cultural dynamics of
Ukrainian society. The application of synergetic approaches to the new “border philosophy” opens the way to the awareness
of spatial invariance and multiculturalism as factors influencing social values and behavioral realities.
It is emphasized that the use of the spatial paradigm provides an introduction to the problem of Ukrainian-Russian
relations in the context of the clash of opposing identities and offers new constructivist approaches to understanding the
role of territorial factors in society. It is proved that the models of territorial identity that emerge on the border under
the influence of geopolitical factors have the capacity to become a stable basis for worldview and value orientations.
Their careful study through the prism of the border phenomenon will shed light on the origins of the political and
socio-humanitarian crisis in Ukrainian-Russian relations, elucidate the mechanisms of controversial social development
vectors, consciousness demarcations and conflicts of interest at state and ethnic borders. In the conditions of modern
“identity wars”, the strategy to minimize on the borders the manifestations of asymmetry of cultures, contexts and
meanings, signs of ambivalence and antinomy, to fight mutually exclusive visions of the past and prospects is represented.
Emphasis is placed on the possibilities of using the border paradigm in state building and restoration of territorial and
structural development of Ukraine after the war, strengthening the consolidation of Ukrainian society, ensuring national
unity and stability.